Foot orthotics in therapy and sport - Hunter, Skip 1948-; Dolan, Michael G. 1959-; Davis, John M. 1951- (Human Kinetics, 1995)
Packed with practical, step-by-step instructions, Foot Orthotics in Therapy and Sport will help you master the art of creating orthotics. The authors - all certified athletic trainers and experts in orthotic fabrication - have written this how-to reference specifically for athletic trainers, physical therapists, and sports physicians. Foot Orthotics in Therapy and Sport features important background information for beginners, outlining the latest theories, approaches, and techniques for making braces and supports. And for more seasoned fabricators, there is a wealth of new ideas to use in your practice. Whether you're just starting out or you're a seasoned sports clinician, Foot Orthotics in Therapy and Sport presents easy, hands-on instructions for making state-of-the-art orthotics.